The Effect of Price Perception, Product Quality, Service Quality On Consumer Loyalty Mediated By Consumer Satisfaction - BR Ginting, Yohana Ribka; Heryjanto, Andreas (CV. Publikasi Indonesia, 2023)
The study aims to analyze customer satisfaction and test customer loyalty which is influenced by perceived price, product quality and service quality based on the reputation of salted fish sellers in the BSD Modern Market. In this study, the technique of taking data sources by means of non probability sampling with purposive sampling method. The sample used is salted fish buyers in the BSD modern market - Tangerang with a productive age of 20-65 years collected through questionnaires, totaling 160 respondents. This study uses Partial Least Squares SEM or what is called PLS-SEM and identifies the relationship between variables as well as conceptual and operational definitions using previous research, which includes using the variables of price perception, product quality, and service quality as independent variables, customer loyalty as the dependent variable, and customer satisfaction as the intervening variable. The results of this study indicate that price perception has a positive, but insignificant effect on consumer loyalty and product quality has a positive, but insignificant effect on consumer loyalty, while service quality has a positive and significant effect on consumer loyalty. Price perceptions, product quality and service quality have a positive and significant effect on customer satisfaction. Price perceptions, product quality and service quality have a positive and significant effect on consumer loyalty mediated by salted fish consumer satisfaction in BSD Modern Market - Tangerang